Recent developments in intra-CDCC trade (ECLAC Port of SpainTT, 2001)
Analyses the evolution of aggregate intra-CDCC trade in goods during the 1990s. Attempts to examine the commodity composition of trade where data is available. Focuses on the impact of recent developments in the countries' trade policies on trade performance.
Bibliography: p. 39